Higher Pathological Complete Response Rate of Less than 10 Total Axillary Lymph Nodes After Axillary Lymph Node Dissection Following Neoadjuvant Chemotherapy in Breast Cancer - Jeeyeon Lee; Jeeyeon Lee; Nora Jee-Young Park; Nora Jee-Young Park; Byeongju Kang; Byeongju Kang; Jin Hyang Jung; Jin Hyang Jung; Wan Wook Kim; Wan Wook Kim; Yee Soo Chae; Yee Soo Chae; et al. (Frontiers in Surgery, 2022)
BackgroundThe American Joint Committee on Cancer (AJCC) guideline recommends the evaluation of ≥10 axillary lymph nodes (ALN) in patients with breast cancer to assess the N stage. However, the total ALN count in ALN dissection (ALND) often decreases after neoadjuvant chemotherapy in breast cancer. The authors compared clinicopathological factors and oncological outcomes between <10 vs. ≥10 ALNs after ALND following neoadjuvant chemotherapy in breast cancer.MethodsData of 159 patients with breast cancer, treated with neoadjuvant chemotherapy and ALND, were reviewed, and the cases were classified into two groups (<10 vs. ≥10 ALN count). The treatment response was determined based on the RECIST 1.1 criteria, and histopathological regression of the tumor was assessed based on the Miller-Payne grading scales.ResultsMost of the clinical and pathological factors did not demonstrate any significant differences between the two groups. However, the pathological complete response (pCR) rate in breast lesion and ALNs were the higher trend in the group with <10 ALNs. During the 88-month follow-up period, there was no significant difference in locoregional recurrence, distant metastasis, or overall survival.ConclusionsAlthough there was a limitation due to different sample sizes, additional axillary surgery may not be necessary even in cases with <10 total ALNs after ALND, following neoadjuvant chemotherapy because the lymph nodes are more likely to have been regressed themselves due to neoadjuvant chemotherapy, and the residual lymph nodes may be absent.